A REAL-TIME LICENSE PLATE DETECTION SYSTEM FOR PARKING ACCESS - Fajar Astuti Hermawati; Roenadi Koesdijarto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
The automatic and real-time license plate detection system can be used as an access control entry of vehicles into the parking area. The problem is how to recognize the vehicles that will go into the parking lot and how to recognize various types of license plates in various light conditions quickly and accurately. In this research, the prototype was developed with a detection system to recognize the vehicles that will enter the parking area, and a license plate recognition system. In the license plate recognition system, the Fourier transform and Hidden Markov model method have proposed to detect location of license plate and as  characters segmentation to recognize Indonesia license plates. The research results have shown that the developed prototipe system has successfully recognized all Indonesia license plates in several of light condition and camera position. The percentage of plate recognition in the real-time experiment is 84.38%, and the average execution time for all recognition process is 5.834 second.